Recent Developments and Advancements in Graphene-Based Technologies for Oil Spill Cleanup and Oil–Water Separation Processes - Salma Elhenawy (18810343) (2021)
The vast demand for petroleum industry products led to the increased production of oily wastewaters and has led to many possible separation technologies. In addition to production-related oily wastewater, direct oil spills are associated with detrimental effects on the local ecosystems. Accordingly, this review paper aims to tackle the oil spill cleanup issue as well as water separation by providing a wide range of graphene-based technologies. These include graphene-based membranes; graphene sponges; graphene-decorated meshes; graphene hydrogels; graphene aerogels; graphene foam; and graphene-coated cotton. Sponges and aerogels modified by graphene and reduced graphene oxide demonstrated effective oil water separation owing to their superhydrophobic/superoleophilic properties. In addition, oil particles are intercepted while allowing water molecules to penetrate the graphene-oxide-coated metal meshes and membranes thanks to their superhydrophilic/underwater superoleophobic properties. Finally, we offer future perspectives on oil water separation that are hindering the advancements of such technologies and their large-scale applications. Other Information Published in: Nanomaterials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/nano12010087